The end of a long controversy? (Mayéutica Revista Científica de Humanidades y Artes, 2024)
The year 2023 culminates with two electoral events of different sign and content: a primary election held by the opposition sectors to and content: a primary election held by the opposition sectors to choose their candidate for the 2024 presidential to choose their candidate for the 2024 presidential elections, and a consultative referendum, called by the Venezuelan consultative referendum, called by the Venezuelan government on the controversy with Guyana over sovereignty in the over sovereignty in the Essequibo. The opposition primary elections should be understood -despite the judicial response of the Government, as an act of exercise of citizenship, proper of any exercise of citizenship, proper of any political system that prides itself on being democratic; but in relation to that of the opposition, the primary democratic political system; but in relation to the delicate situation of Venezuela's historical claim to the historical claim over the Essequibo territory, it is necessary to have a reading with a State vision that transcends the current State that transcends the current political conjuncture. It is a territorial dispute, as established in the Geneva Agreement signed by Venezuela and the British Crown in 1966, an undeniable diplomatic achievement of the governments of Presidents Rómulo Betancourt and Raúl Leoni, since in this document Great Britain recognizes the irregularity of the Arbitral Award of 1899 and opens the doors to an international and diplomatic arbitration solution to a territorial problem.  international and diplomatic arbitration solution to a territorial problem that is now 180 years old.